2011
DOI: 10.1212/cpj.0b013e31823b4e5d
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime neurotoxicity can mimic postanoxic coma with myoclonic status epilepticus

Abstract: A 61-year-old woman admitted for operative treatment of aortic and mitral stenosis and coronary artery bypass grafting developed encephalopathy and abnormal movements postoperatively. The evening after surgery, she was hypoxic and hypotensive. The following day, she was awake and following commands without any obvious focal deficits. Over subsequent days her mental status worsened as she remained in shock. Hypoperfusion of the kidneys and liver resulted in acute tubular necrosis and transaminitis. On postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Indeed, in a retrospective study, it was reported that non‐epileptic events such as tremor‐like movements, multifocal myoclonic jerks without electrographic changes, and slow semi‐purposeful movements of the limbs or trunk, frequently mimic seizures in the ICU setting, and only bedside v‐EEG recordings may help in the differential diagnosis (Benbadis et al , 2010). Interestingly, similar movements to those described by Hocker and Rabinstein (2011) ( e.g. sudden and forceful opening and closing of the jaw) mimicking post‐anoxic coma may also be observed in the video reported here.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, in a retrospective study, it was reported that non‐epileptic events such as tremor‐like movements, multifocal myoclonic jerks without electrographic changes, and slow semi‐purposeful movements of the limbs or trunk, frequently mimic seizures in the ICU setting, and only bedside v‐EEG recordings may help in the differential diagnosis (Benbadis et al , 2010). Interestingly, similar movements to those described by Hocker and Rabinstein (2011) ( e.g. sudden and forceful opening and closing of the jaw) mimicking post‐anoxic coma may also be observed in the video reported here.…”
Section: Discussionsupporting
confidence: 88%
“…It is not unusual to doubt the existence of hypoxic or hypotensive complications in critically ill subjects. This point is crucial when one makes a decision regarding the aggressiveness of treatment and prognostication (Hocker and Rabinstein, 2011). It is widely known that the prognosis of acute MSE after cardiac arrest is poor, and intensive treatment does not modify outcome at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations